Insights from low‐temperature thermochronometry into transpressional deformation and crustal exhumation along the San Andreas fault in the western Transverse Ranges, California. Issue 6 (20th December 2013) - Niemi, Nathan A.; Buscher, Jamie T.; Spotila, James A.; House, Martha A.; Kelley, Shari A.
Abstract [1] The San Emigdio Mountains are an example of an archetypical, transpressional structural system, bounded to the south by the San Andreas strike‐slip fault, and to the north by the active Wheeler Ridge thrust. Apatite (U‐Th)/He and apatite and zircon fission track ages were obtained along transects across the range and from wells in and to the north of the range. Apatite (U‐Th)/He ages are 4–6 Ma adjacent to the San Andreas fault, and both (U‐Th)/He and fission track ages grow older with distance to the north from the San Andreas. The young ages north of the San Andreas fault contrast with early Miocene (U‐Th)/He ages from Mount Pinos on the south side of the fault. Restoration of sample paleodepths in the San Emigdio Mountains using a regional unconformity at the base of the Eocene Tejon Formation indicates that the San Emigdio Mountains represent a crustal fragment that has been exhumed more than 5 km along the San Andreas fault since late Miocene time. Marked differences in the timing and rate of exhumation between the northern and southern sides of the San Andreas fault are difficult to reconcile with existing structural models of the western Transverse Ranges as a thin‐skinned thrust system. Instead, these results suggest that rheologic heterogeneities may play a role in localizing deformation along the Big Bend of the San Andreas fault as the San Emigdio Mountains are compressed between the crystalline basement of Mount Pinos and oceanic crust that underlies the southern San Joaquin Valley.